Obstructed Hemivagina and Ipsilateral Renal Agenesis (OHVIRA) Syndrome: A Rare Case Report - Ega Atista; Yulia Margaretta Sari (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: The Herlyn-Werner-Wunderlich (HWW) syndrome, also known as obstructed hemivagina and ipsilateral renal agenesis (OHVIRA), is a rare form of Mullerian Duct Anomalies (MDA). The patient with OHVIRA syndrome has dysmenorrhea, abdominal pain, and a lump in the belly. Although the exact cause and pathology of OHVIRA syndrome are unknown, early diagnosis and treatment can reduce acute symptoms and preserve normal fertility. Case Report: This article reports a case of 15 a 15-year-old woman who complained of foul mucopurulent discharge. Ultrasound finding uterus didelphys, right obstructed hemivagina with resultant pyocolpos, and suspected of right renal agenesis. The patient was diagnosed with OHVIRA syndrome. The patient underwent vaginal septal resection, and the pyocolpos was drained. Discussion: Intraoperatively, a completely obstructed longitudinal vaginal septum was identified on the right hemivagina, with purulent fluid consistent with pyocolpos. After septal resection, adequate drainage was achieved and communication between both hemivaginas was established. Postoperatively, the patient showed clinical improvement, with resolution of vaginal discharge and relief of vaginal obstruction. No intraoperative or immediate postoperative complications were observed. During short-term follow-up, the patient remained asymptomatic, with no evidence of recurrent obstruction or infection. Conclusion: This case highlights several important aspects of OHVIRA syndrome, including its atypical postpartum presentation, diagnostic challenges, and unpredictable reproductive outcomes. Ultrasonography plays a key role in early detection. Vaginal septal resection and drainage are effective in relieving symptoms and preventing complications. Reporting this rare presentation contributes to improved awareness and timely management of OHVIRA syndrome in adolescents.